Risk factors for periprosthetic joint infection of the hip and knee - Jozef Breznicky; Marian Hlavac; Martin Novak; Matej Hrncar (Medicinski glasnik, 2019)
Aim: To investigate risk factors for the development of prosthetic joint infection. Methods: A group of 50 patients with periprosthetic infection was compared with a group of 100 randomly selected patients with total hip or knee arthroplasty without infectious complications. Twelve risk factors in both groups were analysed. Results: Five factors showed to be significant: body mass index higher than 40, diabetes mellitus on insulin therapy, kidney and liver disease, vascular disease of the lower extremities and positive drain tip culture. Conclusion: One of the ways to reduce the incidence of periprosthetic infection is the maximum possible elimination of risk factors in patients who have a high probability of endoprosthesis infection. If this elimination is not possible for a long time, it is advisable to consider abandoning the planned operation.
Keywords: body mass index; diabetes mellitus; total joint replacement